2014
DOI: 10.3109/15419061.2013.876014
|View full text |Cite
|
Sign up to set email alerts
|

Trafficking Highways to the Intercalated Disc: New Insights Unlocking the Specificity of Connexin 43 Localization

Abstract: With each heartbeat, billions of cardiomyocytes work in concert to propagate the electrical excitation needed to effectively circulate blood. Regulated expression and timely delivery of connexin proteins to form gap junctions at the specialized cell – cell contact region, known as the intercalated disc, is essential to ventricular cardiomyocyte coupling. We focus this review on several regulatory mechanisms that have been recently found to govern the lifecycle of connexin 43 (Cx43), the short-lived and most ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 150 publications
(210 reference statements)
2
16
0
Order By: Relevance
“…As shown in Fig. 7, immunoreactive signals for SAP97 were concentrated at the cell surface in control myocytes, similar to the previously reported localization of this protein to intercalated discs in adult rat ventricular myocardium (22). However, there was a marked decrease in the amount of SAP97 signal at the cell surface in myocytes expressing 2057del2 plakoglobin, which was fully reversed by exposing myocytes to SB216763 for 24 hours (Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…As shown in Fig. 7, immunoreactive signals for SAP97 were concentrated at the cell surface in control myocytes, similar to the previously reported localization of this protein to intercalated discs in adult rat ventricular myocardium (22). However, there was a marked decrease in the amount of SAP97 signal at the cell surface in myocytes expressing 2057del2 plakoglobin, which was fully reversed by exposing myocytes to SB216763 for 24 hours (Fig.…”
Section: Resultssupporting
confidence: 90%
“…This suggests a unique relationship between plakoglobin and SAP97 not shared by other desmosomal linker proteins. Finally, knockdown of SAP97 expression had no effect on the distribution of Cx43, whose trafficking is known to involve a different transport mechanism (22). …”
Section: Resultsmentioning
confidence: 99%
“…Targeted delivery of ion channels to the appropriate subdomain requires three components: a cytoskeleton delivery apparatus, a membrane anchor, and the channel itself 11, 38 . Previously, we identified that key components of targeted delivery of Cx43 hemichannels to the ventricular intercalated disc include microtubules which are captured by the membrane anchor adherens junctions complex including N-Cadherin, β-catenin and p150 (Glued) 17, 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence supports a cytoskeletal-based trafficking mechanism for Cx43 delivery directly to the intercalated disc 10, 11 . It is understood that Cx43 hemichannels oligomerize in the trans-Golgi network 12 , and are subsequently packaged into vesicles transported by motor proteins along microtubules 1315 .…”
Section: Introductionmentioning
confidence: 99%
“…We cannot rule out that other pathways of Cx43 trafficking and GJ life cycle, besides phosphorylation, are affected, including microtubule-dependent forward trafficking to the junctional plaques. 36…”
Section: Potential Molecular Mechanismmentioning
confidence: 99%